1992
DOI: 10.1164/ajrccm/146.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-2 on the Airway Response to Antigen in the Rat

Abstract: To evaluate the hypothesis that lymphocyte stimulation can modify the bronchoconstrictive response to inhalational challenge with an allergen, we administered interleukin-2 (IL-2), an important lymphokine in lymphocyte activation and proliferation, to actively sensitized rats. Brown Norway rats received either human recombinant IL-2 (n = 8) or its vehicle (n = 7) twice a day from the ninth to the fourteenth day after active sensitization to ovalbumin (OA) and were challenged with an aerosol of OA. Lung resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…IL-2 causes lymphocyte activation and proliferation and affects the regulation of immunoglobulin production and lymphokine expression related to the activation of other cells. It has been reported that IL-2 administration induced OVA-specific IgG production and airway inflammation [26]. In addition, T-cells from eosinophilic patients produce IL-5 after IL-2 stimulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 causes lymphocyte activation and proliferation and affects the regulation of immunoglobulin production and lymphokine expression related to the activation of other cells. It has been reported that IL-2 administration induced OVA-specific IgG production and airway inflammation [26]. In addition, T-cells from eosinophilic patients produce IL-5 after IL-2 stimulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, administration of exogenous IL-2, a potent T cell growth factor, resulted in enhancement of LARs in the Brown Norway (BN) rat (14). This study suggested that the activation of T cells by IL-2 and the subsequent release of other T cell cytokines might directly modulate the LAR.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that these effects were observed in vitro, but gedunin treatment also resulted in diminished numbers of activated T lymphocytes in draining lymph nodes and in the allergic tissue. During allergic responses, the number of T cells increase in the lymph nodes, as a consequence of antigen presentation and clonal expansion, which is followed by the migration of antigen-specific T lymphocytes into the inflamed site [47,48]. Resident T cells are activated at the site of allergen deposition and mediate the local response to allergen, which is amplified by the arrival of new T lymphocytes in the target tissue [49][50][51].…”
Section: Discussionmentioning
confidence: 99%